Influences of ecology and biogeography on shaping the distributions of cryptic species: three bat tales in Iberia. (16th April 2014) - Santos, Helena; Juste, Javier; Ibáñez, Carlos; Palmeirim, Jorge M.; Godinho, Raquel; Amorim, Francisco; Alves, Pedro; Costa, Hugo; de Paz, Oscar; Pérez-Suarez, Gonzalo; Martínez-Alos, Susana; Jones, Gareth; et al.
Abstract: To determine what shapes the distributions of cryptic species, we aimed to unravel ecological niches and geographical distributions of three cryptic bat species complexes in Iberia, Plecotus auritus / begognae, Myotis mystacinus / alcathoe and Eptesicus serotinus / isabellinus (with 44, 69, 66, 27, 121 and 216 records, respectively), considering ecological interactions and biogeographical patterns. Species distribution models (SDMs) were built using a presence-only technique (Maxent), incorporating genetically identified species records with environmental variables (climate, habitat, topography). The most relevant variables for each species' distribution and respective response curves were then determined. SDMs for each species were overlapped to assess the contact zones within each complex. Niche analyses were performed using niche metrics and spatial principal component analyses to study niche overlap and breadth. The Plecotus complex showed a parapatric distribution, although having similar biogeographical affinities (Eurosiberian), possibly explained by competitive exclusion. The Myotis complex also showed Eurosiberian affinities, with high overlap between niches and distribution, suggesting resource partitioning between species. Finally, E. serotinus was associated with Eurosiberian areas, while E. isabellinus occurred in Mediterranean areas, suggesting possible competition in their restricted contact zone. This study highlights the relevance of considering potential ecological interactions between similarly ecological species when assessing species distributions. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 150–162.